IMPLEMENTASI PENDEKATAN HOLISTIK TERHADAP PERKEMBANGAN SISWA DI TAMAN KANAK-KANAK AL-AZZAM MUNJUL PANDEGLANG - Neng Ade Rodiawati; Sifa Muziah; Mumu Zainal Mutaqin (LPPM Institut Nida El-Adabi, 2025)
This study aims to determine how the application of a holistic approach in learning is used and its impact on student development at Al-Azzam Kindergarten Munjul Pandeglang. This research emphasizes the importance of developing children's potential as a whole, which includes cognitive, affective, psychomotor, emotional, social, and spiritual aspects. Using descriptive qualitative methods, data were collected through interviews, observations, and documentation involving teachers as participants in the learning process. Analysis followed the stages of data reduction, presentation, and conclusion drawing. The results show that the holistic approach improves children's understanding of life values, fosters moral character, and builds strong social awareness. The results of this study indicate that holistic learning is very relevant for early childhood education, as it makes a significant contribution in shaping individuals who have strong faith and integrity.